Chairetismos: En byzantinsk formel-melisme med særlige karaktertræk - Jung, Annette (Danish Yearbook of Musicology, 1999)
Chairetismos – a Byzantine Formulaic Melism with Distinctive Features During an investigation of the long melisms in the otherwise syllabic melodies used for the monostrophic church poem known as a sticheron, it was found that the melism chairetismos had a certain connection with the literary genre chairetismoi, where it embellished the χαιρε (chaire, hail) at the beginning of a verse. This poetic genre is modelled on the Annunciation text in Luke 1,28, and a line of chairetismoi expresses a dogmatic theological interpretation of the nature of the Virgin Mary (Theotokos), but the form may also be transferred to hymns of apostles and saints. Besides its use with chairetismoi, chairetismos also functions in the same way as the other melisms in the sticheron genre. There is a tendency for chairetismos to be confused with another melism, thema haploun. The two melisms are clearly kept apart in the adiastematic Palaeobyzantine Chartres notation, but notated with the same group of neumes in the adiastematic Palaeobyzantine Coislin notation. The distinction between the two melisms is re-established in the universal diastematic round notation after about 1170, but an ambiguous melism, which may equally be interpreted as chairetismos or thema haploun, appears in this notation. A late Byzantine theorist showed, however, that this melism is just an alternative to chairetismos.